A Target-Based Spin Pass Training Model for Passing Accuracy in Rugby - Handy Nacha Ratmaja; Dinar Dinangsit; Encep Sudirjo (Journal Coaching Education Sports, 2026)
This study was motivated by the low passing ability, particularly in the spin pass technique, among university rugby athletes, as indicated by poor directional accuracy, inadequate throwing power, and limited ball control. Therefore, this study aimed to examine the effect of a target-based spin pass training model on passing accuracy in rugby. The study employed a quantitative approach using a quasi-experimental one-group pretest–posttest design. The participants consisted of 14 university rugby athletes selected through purposive sampling. The intervention was conducted over 12 training sessions using a target-based spin pass training program. Passing accuracy was measured using a fixed-target spin pass test with established validity. Data were analyzed using descriptive statistics, normality testing, paired sample t-tests, and effect size analysis. The findings revealed a significant improvement in passing accuracy, with the mean score increasing from 9.63 in the pretest to 12.39 in the posttest. The paired sample t-test showed a significant difference between pretest and posttest scores (t = -4.911, p < 0.05). In addition, the effect size indicated a strong practical impact of the intervention on passing performance. These findings suggest that the target-based spin pass training model is effective in improving rugby passing accuracy and can be recommended as an innovative and structured training method for university rugby athletes.